Os assalariados rurais da agroindústria canavieira na mesorregião noroeste paranaense - Carvalho, Josiane Fernandes de (2008)
Although there is a wide production on the unfolding of the agriculture modernization process in space, it is necessary to recognize that there are particularities which are territorialy imposed. Within this sense, the present study contributes with some considerations that are specific to work relations, which are modified with the territorialization of the sugarcane agroindustry, especially in the formation of the rural employee of sugarcane cut. For this reason, the Nothwest Mesoregion of "Paraná" was delimited as the reachable area, due to specificities of the capitalism development process in the field of this region. Thus, it was objectified to realize a historical review about work relations in the rural area and the occupation of the region, considering the structuralization of that area, starting with the small property, and the work relations that are not supported by the salary. From this on, it starts to analyze the consolidation of the sucroalcohol sector as the detentor of capital and the greater personification of the rural employee exploitation in the northwest of "Paraná". Therefore, it presents the differentiations that are territorialy expressed from the relation between the agroindustrial capital of the sugarcane plantation and the rural employee who works with the sugarcane plantation, understanding the fragmentation of the work process in the new spatial and social rearrangement